PENENTUAN UMUR SIMPAN SIRUP PALA BERDASARKAN PERUBAHAN DERAJAT KEASAMAN pH - Melisa J. Sahambangung; Lady Ch. Lengkey; David Rumambi (COCOS, 2016)
ABSTRACTNorth Sulawesi province known as one of the largest producer of nutmeg crop in Indonesia. North Sulawesi supplies about 75% of the needs of nutmeg world with exports ranging between 1000 to 2000 tons. Processing nutmeg nutmeg syrup is one way of diversification of nutmeg. Small and Medium Industries (SMI) "Sari Fruit" is one nutmeg syrup producers in North Sulawesi, especially in the district of Sitaro. However nutmeg syrup products on the market has not been specified expiration date. One method that can be used in determining the shelf life of foodstuffs is ASLT (Accelerated Shelf Life Testing). The benefits of this research is to increace public knowledge about the processing of nutmeg syrup, and to add nutmeg syrup product competitiveness. The nutmeg syrup stored at a temperature of 30 ° C, 35 ° C and 40 ° C for 12 weeks (90 days). The parameters used to analyze the degradation products are nutmeg syrup, pH. The results showed that the shelf life based on pH nutmeg syrup at normal storage temperature of 30 ° C is 52.48 weeksKey words : nutmeg syrup, ASLT ((Accelerated Shelf Life Testing)